Antigen‐Specific Stimulation and Expansion of CAR‐T Cells Using Membrane Vesicles as Target Cell Surrogates. Issue 45 (3rd October 2021) - Ukrainskaya, Valeria; Rubtsov, Yuri; Pershin, Dmitry; Podoplelova, Nadezhda; Terekhov, Stanislav; Yaroshevich, Igor; Sokolova, Anstasiia; Bagrov, Dmitry; Kulakovskaya, Elena; Shipunova, Victoria; Deyev, Sergey; Ziganshin, Rustam; et al.
Abstract: Development of CAR‐T therapy led to immediate success in the treatment of B cell leukemia. Manufacturing of therapy‐competent functional CAR‐T cells needs robust protocols for ex vivo/in vitro expansion of modified T‐cells. This step is challenging, especially if non‐viral low‐efficiency delivery protocols are used to generate CAR‐T cells. Modern protocols for CAR‐T cell expansion are imperfect since non‐specific stimulation results in rapid outgrowth of CAR‐negative T cells, and removal of feeder cells from mixed cultures necessitates additional purification steps. To develop a specific and improved protocol for CAR‐T cell expansion, cell‐derived membrane vesicles are taken advantage of, and the simple structural demands of the CAR‐antigen interaction. This novel approach is to make antigenic microcytospheres from common cell lines stably expressing surface‐bound CAR antigens, and then use them for stimulation and expansion of CAR‐T cells. The data presented in this article clearly demonstrate that this protocol produced antigen‐specific vesicles with the capacity to induce stronger stimulation, proliferation, and functional activity of CAR‐T cells than is possible with existing protocols. It is predicted that this new methodology will significantly advance the ability to obtain improved populations of functional CAR‐T cells for therapy. Abstract : Antigenic vesicles (AVs) bind specifically to the surface of their cognate CAR‐T cells. The binding of AVs to CAR‐T cells results in the activation and proliferation of CAR‐T cells. AVs induce CAR‐T cells' functional maturation and increase CAR‐T cells' cytotoxic activity. Incubation with AVs results in antigen‐specific expansion of functional CAR‐T cells.